(untitled) (American Journal of Islam and Society, 1992)
Profit-sharing contzacts have recently captured the attention of academicians, bankers, and policymakers, particularly those in the Middle East. These contracts are characterized by risk sharing, an element that forces the contracting parties (especially the financier) to fund only sound projects. The theoretical analyses of such contracts have received a major boost from a variety of models, including Khan (1986) and Haque and Mirakhor (1986), and empirical support from, for example, Darrat (1988) and Bashir et al. (1991). The bold claim of these models is that if the interest payment on financial capital were to be replaced by the profit sharing arrangement, the level of investment would be enhanced instead of weakened. A commonly used profit-sharing financial contract is known as musharakah (equity participation). This contract is a limited partnership in which the investor(s) and the entrepreneur pool their capital to finance a specific investment project. Another version of musharukah involves the investor participating in an existing enterprise by contributing capital. In both cases, the pro-rata distribution of profit is stated in the contract and losses are shared according to capital contribution. The investor is eligible to participate in the project’s management, but may also waive this right.’ A musharakah arrangement can be modeled as a two-person, two-period partnership game. In this setup, each player‘s utility depends on the other player’s action through a commonly observed consequence (profit), which is itself a function of both players’ actions and an exogenous stochastic environment. The game is thus one of decentralized decision making in which individual optimizers ...